The fish embryo toxicity test as a replacement for the larval growth and survival test: A comparison of test sensitivity and identification of alternative endpoints in zebrafish and fathead minnows. (30th April 2015) - Jeffries, Marlo K. Sellin; Stultz, Amy E.; Smith, Austin W.; Stephens, Dane A.; Rawlings, Jane M.; Belanger, Scott E.; Oris, James T.
Abstract The fish embryo toxicity (FET) test has been proposed as an alternative to the larval growth and survival (LGS) test. The objectives of the present study were to evaluate the sensitivity of the FET and LGS tests in fathead minnows (Pimephales promelas) and zebrafish (Danio rerio) and to determine if the inclusion of sublethal metrics as test endpoints could enhance test utility. In both species, LGS and FET tests were conducted using 2 simulated effluents. A comparison of median lethal concentrations determined via each test revealed significant differences between test types; however, it could not be determined which test was the least and/or most sensitive. At the conclusion of each test, developmental abnormalities and the expression of genes related to growth and toxicity were evaluated. Fathead minnows and zebrafish exposed to mock municipal wastewater‐treatment plant effluent in a FET test experienced an increased incidence of pericardial edema and significant alterations in the expression of genes including insulin‐like growth factors 1 and 2, heat shock protein 70, and cytochrome P4501A, suggesting that the inclusion of these endpoints could enhance test utility. The results not only show the utility of the fathead minnow FET test as a replacement for the LGS test but also provide evidence that inclusion of additional endpoints could improve the predictive power of the FET test. Environ Toxicol Chem 2015;34:1369–1381. © 2015 SETAC